Deaths of young people living in residential aged care: a national population-based descriptive epidemiological analysis of cases notified to Australian coroners. Issue 15 (17th July 2021) - Eastwood, Kathryn; Bugeja, Lyndal; Zail, Joshua; Cartwright, Anna; Hopkins, Alexandra; Ibrahim, Joseph E.
Abstract: Aim: This study provides a descriptive epidemiological analysis stratified by age of deaths reported to Australian Coroners of residential aged care facility residents aged under 65 years. Method: A national population-based retrospective analysis was conducted of deaths of Australian residential aged care facility residents reported to Australian Coroners between 2000 and 2013. Descriptive statistics compared adult residents categorised using age by factors relating to the individual, incident and death investigation. Results: Of the 21, 736 deaths of residential aged care facilities residents aged over 20 years reported to Australian Coroners, 782 (3.6%) were of residents aged 20–64 years. Natural cause deaths occurred at similar rates irrespective of age. Intentional external cause deaths were higher in residents aged 20–64 years (5.3% vs. 16.0%; OR 3.43, 95% CI 2.0–5.9; p  < 0.001), with suicide rates three times that of the over 65 years group (13.2% vs. 4.1%; OR 0.28, 95% CI 0.16–0.51; p  < 0.001). External cause deaths from choking and falls were most common in the younger and older groups respectively. Conclusions: More is required to prevent external cause deaths in young residential care facility residents. IMPLICATIONS FOR REHABILITATION: One in seven (14.1%) deaths of people aged 20–64 years in residential aged care facilities are premature and potentially avoidable. The more common external causes of death include suicide, choking and falls. The prevalence and causes of preventable deaths in this study provide a basis for prompting and developing more specific prevention policies and practices to reduce harm for young people in residential aged care. Specifically, addressing loneliness would improve social inclusion, mental health and suicide risk. Better management of progressive neurological conditions with multidisciplinary team and re-ablement programs would reduce risk of choking and falls. Improving outcomes for young people in residential aged care requires a co-ordinated, multisector approach comprising relevant government departments, aged care providers, researchers and clinicians. Effective planning requires more information about the cause and nature of deaths, and due to the small event counts, this would ideally involve an international collaboration.